2006
DOI: 10.1096/fj.06-6054com
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress exacerbates ischemia‐reperfusion‐induced apoptosis through attenuation of Akt protein synthesis in human choriocarcinoma cells

Abstract: Oxidative stress is central to ischemia-reperfusion injury. The role of the endoplasmic reticulum (ER) in this process is uncertain. In ER signaling, PERK-Nrf2 and Ire-CHOP are two pathways that determine cell fate under stress. PERK-Nrf2 up-regulates antioxidant enzyme expression whereas Ire-CHOP promotes apoptosis. We have identified a novel pathway in ER stress-induced apoptosis after ischemia-reperfusion in vitro involving translational suppression of the survival kinase PKB/ Akt (Akt), and elucidated an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 59 publications
5
118
0
Order By: Relevance
“…22 Recently, we showed that I/R induces ER stress in the human trophoblast-like cell line, JEG-3 choriocarcinoma cells, and that this is associated with inhibition of protein synthesis. 23 One of the consequences we observed was reduced concentrations of both phosphorylated and total AKT. AKT signaling plays a central role in the regulation of cell growth and proliferation by integrating the actions of growth factors and functioning as an ATP and amino acid sensor to fine tune protein synthesis to nutrient availability via control of the mammalian target of rapamycin (mTOR) pathway and glycogen synthase kinase 3 (GSK-3) activity, respectively.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…22 Recently, we showed that I/R induces ER stress in the human trophoblast-like cell line, JEG-3 choriocarcinoma cells, and that this is associated with inhibition of protein synthesis. 23 One of the consequences we observed was reduced concentrations of both phosphorylated and total AKT. AKT signaling plays a central role in the regulation of cell growth and proliferation by integrating the actions of growth factors and functioning as an ATP and amino acid sensor to fine tune protein synthesis to nutrient availability via control of the mammalian target of rapamycin (mTOR) pathway and glycogen synthase kinase 3 (GSK-3) activity, respectively.…”
mentioning
confidence: 82%
“…23 Human choriocarcinoma JAR cells were a gift from Dr. Ashley Moffett and were grown in RPMI 1640 medium (Invitrogen Ltd, Paisley, UK) supplemented with 5% heat-inactivated fetal bovine serum (Invitrogen), penicillin (100 U/ml), and streptomycin (100 g/ml) at 37°C in a 5% CO 2 atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
“…In this issue of the AJP, Yung and colleagues 1 demonstrate that protein synthesis inhibition and ER stress play key roles in the pathophysiology of intrauterine growth restriction. One should also consider the authors' earlier study examining ER stress in the choriocarcinoma cell line JEG-3, 14 which could be induced by deprivation of oxygen and glucose or by tunicamycin. The authors singled out the survival kinase AKT (also known as protein kinase B) for detailed study.…”
mentioning
confidence: 99%
“…Previous studies have commonly reported that endoplasmic reticulum (ER) stress plays a crucial role in the induction and regulation of apoptosis (7,8). There are numerous pathways involved in ER stress, such as ER-associated protein degradation and the unfolded protein response (UPR) (9) The UPR pathway also activates several proteins, including inositol-requiring enzyme (IRE) 1, protein kinase R-like ER kinase (Perk) and activating transcription factor 6 (ATF6) (10).…”
Section: Introductionmentioning
confidence: 99%